2011
DOI: 10.1113/jphysiol.2011.209601
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow alteration in neuroprotection following cerebral ischaemia

Abstract: The best neuroprotectant for acute ischaemic stroke would always be the rapid return of oxygen and glucose to physiological levels. This is currently provided by thrombolysis which restores blood flow to the ischaemic region. The attempt to confer neuroprotection by targeting the brain parenchyma has shown promise in experimental stroke models, but has unequivocally failed to translate to the clinic. Neuroprotective therapy primarily targets the biochemical cascade that produces cell death following cerebral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 61 publications
2
31
0
3
Order By: Relevance
“…Spontaneous hemodynamic fluctuations within the infarct exhibited significant attenuation over most of the functional connectivity band while the remaining components displayed delayed correlations with contralateral brain regions. These observations are consistent with several other studies reporting alterations in neurovascular coupling following stroke[36] in animals and humans where focal ischemia produced regional changes in basal perfusion[3739] and cerebrovascular reactivity[40] within lesional and perilesional tissue. Such physiological effects do not exclude the possibility that viable neuronal tissue may still be present within the ischemic core and surrounding regions.…”
Section: Discussionsupporting
confidence: 92%
“…Spontaneous hemodynamic fluctuations within the infarct exhibited significant attenuation over most of the functional connectivity band while the remaining components displayed delayed correlations with contralateral brain regions. These observations are consistent with several other studies reporting alterations in neurovascular coupling following stroke[36] in animals and humans where focal ischemia produced regional changes in basal perfusion[3739] and cerebrovascular reactivity[40] within lesional and perilesional tissue. Such physiological effects do not exclude the possibility that viable neuronal tissue may still be present within the ischemic core and surrounding regions.…”
Section: Discussionsupporting
confidence: 92%
“…20,26 Similarly, compounds that indirectly affect and improve cerebral blood flow (again including MK801) can confer protection by reducing the severity of the insult rather than exhibiting their purported pharmacological mechanism of action on the brain parenchyma. 27,28 There are also pharmacokinetic differences that need to be taken into account when translating findings to the clinical setting. This can be highlighted by the very promising neuroprotective free radical scavenger, NXY-059; although developed with a preclinical design that addressed many previous limitations, its ability to cross the blood-brain barrier (BBB) and exert its effects in the brain was never clearly demonstrated in humans.…”
Section: Reasons Behind Past Failuresmentioning
confidence: 99%
“…13 This demonstrates the importance of CBF to the outcome after cerebral ischemia, and that neuroprotective agents may actually modulate CBF to produce their effect. 31 Our data revealed that other parameters such as percentage body weight loss, neuroscore, and the number of PIDs were also correlated with infarction ( Figures 3 and 4). However, it may be the total duration of tissue depolarization and not its frequency that correlates with ischemic injury.…”
Section: Discussionmentioning
confidence: 58%